High-speed thrills : acceleration and velocity - Lepora, Nathan (Pleasantville, NY : Gareth Stevens Pub., 2008)
Explains forces of physics through the description of roller coasters, discussing force, speed, acceleration, mass, inertia, friction, air resistance, and braking.
Includes index.
6.7
5-8
Keywords: Acceleration (Mechanics) -- Juvenile literature; Speed -- Juvenile literature; Speed; Speed